1996
DOI: 10.1002/(sici)1097-4628(19960705)61:1<9::aid-app2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mass control in methacrylic copolymer latexes containing glycidyl methacrylate

Abstract: SYNOPSISResults are presented on the preparation and characterization of batch emulsion copolymers of butyl methacrylate and glycidyl methacrylate (GMA). The two main problems occurring during an emulsion copolymerization with GMA are partial hydrolysis of the epoxy groups and internal crosslinking of the latex particles formed. The influence of chain transfer agents (CTA) on the degree of crosslinking was investigated. Furthermore, the effect of reaction temperature and the addition of methacrylic acid on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Therefore, in further reactions, it was decided to reduce the GMA concentration, since this behavior was attributed to possible interactions of the epoxy group with the surfactant that led to colloidal instability. The copolymerization procedure that was finally used was similar to the homopolymerization method with some differences and characteristics that follow: to avoid or reduce the cross-linking reactions associated with the GMA as well as the colloidal instability, sodium bicarbonate was added to the SDBS aqueous solution to increase the pH of the reaction mixture; , the reaction temperature was decreased to 105 °C; in the NMP reactions ( RXN 2 and RXN 3 ), TEMPO was replaced by N - tert -butyl- N -(2-methyl-1-phenylpropyl)- O -(1-phenylethyl) hydroxylamine (universal alkoxyamine, UA); and in the RAFT reactions ( RXN 4 and RXN 5 ), 0.4303 g (1.066 mmol) of 4-cyano-4-(do­decyl­sulfanyl­thiocarbonyl)­sulfanylpentanoic acid as RAFT agent were employed and the KPS initiator was replaced by 0.0164 g (0.068 mmol) of benzoyl peroxide and 0.0432 g (0.222 mmol) of tert -butyl perbenzoate ( RXN 4 ) (to ensure the continuous presence of radicals during the reaction and maintain the living-dormant equilibrium). During the stage of continuous monomer addition (semicontinuous regime), a smaller flow was used in some reactions, compared to the homopolymer case, to end up with a lower solids content in the latex (15%–19%). Isoprene monomer was added first and, immediately after its addition ended, the GMA addition started.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in further reactions, it was decided to reduce the GMA concentration, since this behavior was attributed to possible interactions of the epoxy group with the surfactant that led to colloidal instability. The copolymerization procedure that was finally used was similar to the homopolymerization method with some differences and characteristics that follow: to avoid or reduce the cross-linking reactions associated with the GMA as well as the colloidal instability, sodium bicarbonate was added to the SDBS aqueous solution to increase the pH of the reaction mixture; , the reaction temperature was decreased to 105 °C; in the NMP reactions ( RXN 2 and RXN 3 ), TEMPO was replaced by N - tert -butyl- N -(2-methyl-1-phenylpropyl)- O -(1-phenylethyl) hydroxylamine (universal alkoxyamine, UA); and in the RAFT reactions ( RXN 4 and RXN 5 ), 0.4303 g (1.066 mmol) of 4-cyano-4-(do­decyl­sulfanyl­thiocarbonyl)­sulfanylpentanoic acid as RAFT agent were employed and the KPS initiator was replaced by 0.0164 g (0.068 mmol) of benzoyl peroxide and 0.0432 g (0.222 mmol) of tert -butyl perbenzoate ( RXN 4 ) (to ensure the continuous presence of radicals during the reaction and maintain the living-dormant equilibrium). During the stage of continuous monomer addition (semicontinuous regime), a smaller flow was used in some reactions, compared to the homopolymer case, to end up with a lower solids content in the latex (15%–19%). Isoprene monomer was added first and, immediately after its addition ended, the GMA addition started.…”
mentioning
confidence: 99%
“…Isoprene monomer was added first and, immediately after its addition ended, the GMA addition started. Regarding the addition of sodium bicarbonate as pH buffer, German et al reported the addition of NaHCO 3 to GMA copolymerization reactions to get better stability in the emulsions, avoiding the formation of methacrylic acid from the methacrylic monomers, which may lead to an unfavorable shift in the acid–base equilibrium of the emulsifier, destabilizing the emulsion. In addition, at relatively high concentrations of GMA in acid media, the epoxy group may undergo acidic hydrolysis and further reaction with other epoxy groups leading to polymer cross-linking, so the pH of the media must be carefully adjusted to avoid colloidal instability and/or cross-linking.…”
mentioning
confidence: 99%
See 1 more Smart Citation